Scrivener's moon : the third book in the Fever Crumb series - Reeve, Philip (Reeve, Philip. Fever Crumb series, 2012)
When she returns home after two years, Fever finds that her Scriven mother's creation, New London, the city on wheels, is nearly complete and ready to fight the nomad tribes of Britain--and Fever must journey to the north to find the ancient birthplace of the Scriven mutants and solve the mystery of her own past.